Toward a Multiscale Description of Microvascular Flow Regulation: O2-Dependent Release of ATP from Human Erythrocytes and the Distribution of ATP in Capillary Networks - Goldman, Daniel; Fraser, Graham M.; Ellis, Christopher G.; Sprague, Randy S.; Ellsworth, Mary L.; Stephenson, Alan H. (Frontiers in Physiology, 2012)
Integration of the numerous mechanisms that have been suggested to contribute to optimization of O2 supply to meet O2 need in skeletal muscle requires a systems biology approach which permits quantification of these physiological processes over a wide range of length scales. Here we describe two individual computational models based on in vivo and in vitro studies which, when incorporated into a single robust multiscale model, will provide information on the role of erythrocyte-released ATP in perfusion distribution in skeletal muscle under both physiological and pathophysiological conditions. Healthy human erythrocytes exposed to low O2 tension release ATP via a well characterized signaling pathway requiring activation of the G-protein, Gi, and adenylyl cyclase leading to increases in cAMP. This cAMP then activates PKA and subsequently CFTR culminating in ATP release via pannexin 1. A critical control point in this pathway is the level of cAMP which is regulated by pathway-specific phosphodiesterases. Using time constants ( 100ms) that are consistent with measured erythrocyte ATP release, we have constructed a dynamic model of this pathway. The model predicts levels of ATP release consistent with measurements obtained over a wide range of hemoglobin O2 saturations (sO2). The model further predicts how insulin, at concentrations found in prediabetes, enhances the activity of PDE3 and reduces intracellular cAMP levels leading to decreased low O2-induced ATP release from erythrocytes. The second model, which couples O2 and ATP transport in capillary networks, shows how intravascular ATP and the resulting conducted vasodilation are affected by local sO2, convection and ATP degradation. This model also predicts network-level effects of decreased ATP release resulting from elevated insulin levels. Taken together, these models lay the groundwork for investigating the systems biology of the regulation of microvascular perfusion distribution by erythrocyte-derived ATP.